DIFFERENCES BETWEEN THE MOTOR AND SPECIFIC MOTOR SKILLS OF MONTENEGRIN HANDBALL PLAYERS CONTINENTAL REGIONS AGED 14-15 YEARS - Aldijana Muratović; Jovica Petković; Ivan Vasiljević; Danilo Bojanić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The main objective of this study was to determine the differences in the general motor and specific-motor skills of young handball players. Handball is one of the most popular sports in Montenegro. Given that Montenegro is divided into the continental and mediterranean region in this paper was carried out research relating to young handball players continental areas. Modern handball is exceptionally quick and explosive and is made up of varying physically intense movements which require high level motor skills, both basic and specific (Czerwinski, 1995). The sample makes a total of 50 handball players divided into two groups. The first group consists of 25 handball HC "Sutjeska" from Niksic, aged 14 ± 6 months, while the second group consists of 25 handball HC "Berane" Berane age 15 ± 6 months. Players compete in the Montenegrin cadet league.Motoric space is treated with 10 variables that hypothetically cover the space of: segmented speed, flexibility, explosive leg power, explosive power of arm and shoulder and coordination. The space of specific motoric abilities is tested with 3 variables that hypotetically cover the space of: the ability of manipulating the ball, speed in ball control in movement and speed of movement without ball. Data obtained from the tests is calculated on basic statistic approaches. Comparative statistics is used in the manifest space: t-test arithmetic between small independent samples. Results obtained by the conducted analyzes indicate the existence of statistically significant difference between the fourteen year old and fifteen-year-handball players continental regions. A statistically significant difference was found in 6 variables (hand tapping, long jump, high jump with seats, side steps, ability in throwing and catching balls rejected from the wall and move the triangle basic defensive attitude) out of 13 applied. In previous studies the differences were analyzed between the handball players of different ages (Vuleta, Milanovic & Nikolic, 2012), as well as the differences between the different ranks of competition (Vuleta, Milanovic & Jukic, 1999), where the results show that there are statistically significant differences in the area of motor and specific -motoric abilities. In this paper, statistically significant difference was found in six tests in favor of the fourteen year old handball, what can we explain that in the training process may prevail and other factors such as motivation, which is a very important domain of psychological preparation of athletes.